Prevalence of arteriovenous fistula use in hemodialysis patients in Burdur province - Ateşsaçan, Burak; Rahman, Ömer Faruk; Akgöl, Cüneyt (The European Research Journal, 2025)
Objective: This study aimed to examine the vascular access routes used by patients undergoing hemodialysis treatment in our province and determine the prevalence of arteriovenous (AV) fistula use. Methods: Patients who were receiving regular hemodialysis treatment in Burdur province as of April 2024 were included in the study. Data on patients' age, gender, comorbidities, duration of dialysis, type of vascular access, and history of hemodialysis access were retrospectively reviewed and recorded using electronic patient records. Results: The mean age of 197 patients evaluated in the study was 62.48±14.13 years. Of the patients, 63 (32%) were female and 134 (68%) were male. Hypertension was the most common comorbidity in 61.9% of the cases. The number of patients receiving hemodialysis treatment through an AV fistula was 136 (69%). The mean age of patients receiving treatment via an AV fistula was significantly lower than those receiving treatment via an indwelling hemodialysis catheter (P=0.011). Among the patients treated with an indwelling hemodialysis catheter, 59% had no history of AV fistula surgery. The mean age of patients without a history of AV fistula surgery was statistically significantly higher than those with a history of AV fistula surgery (69.28±14.98 vs. 60.96±13.52, respectively; P=0.001). Conclusions: This study shows that one out of every two patients undergoing hemodialysis through an indwelling hemodialysis catheter has no history of AV fistula surgery. Reaching these patients and prioritizing AV fistula planning is crucial for achieving long-term success in hemodialysis treatment and reducing complications.